Analysis Of The Utilization Of Digitalmarketing In Increasing Gayo Coffee Farmers' Income (Study On Pepalang Village, Takengon City) - Kartini Harahap; Ihsanilma Ihsanilma (Journal of Economics and Business (JECOMBI), 2023)
One of the agricultural products that contributes significantly to the economy in terms of income for the country is coffee. One of the cities in Aceh Province that produces coffee is the city of Takengon with Gayo coffee. One of the villages is said to not have the word prosperous in terms of farmers' income, namely Pepalang village. The income from coffee farming has decreased, resulting in the inability to meet the needs of farmers because the demand for food, plantations, children's school fees and others must be incurred. Farmers are still classified as conventional in doing the work, either by farming, selling coffee and managing coffee. The purpose of this study is to analyze the use of digital marketing as an effort to increase the income of Gayo coffee farmers (a study in Pepalang village, Takengon city) with digital marketing indicators including Accessibility, Interactivity, Entertainment, Credibility, Irritation and Informativeness. This study uses qualitative methods to describe the phenomena that occur. The data collection techniques used in this study are interviews, observation and documentation. This study collects information from interviewing informants consisting of key informants, main informants and additional informants. The data analysis technique uses the process of data reduction, data presentation and drawing conclusions. The results show that the use of digital marketing has an impact, namely it can increase the income of Gayo coffee farmers, Pepalang village, Takengon city. This study uses qualitative methods to describe the phenomena that occur. The data collection techniques used in this study are interviews, observation and documentation. This study collects information from interviewing informants consisting of key informants, main informants and additional informants. The data analysis technique uses the process of data reduction, data presentation and drawing conclusions. The results show that the use of digital marketing has an impact, namely it can increase the income of Gayo coffee farmers, Pepalang village, Takengon city. This study uses qualitative methods to describe the phenomena that occur. The data collection techniques used in this study are interviews, observation and documentation. This study collects information from interviewing informants consisting of key informants, main informants and additional informants. The data analysis technique uses the process of data reduction, data presentation and drawing conclusions. The results show that the use of digital marketing has an impact, namely it can increase the income of Gayo coffee farmers, Pepalang village, Takengon city. The data analysis technique uses the process of data reduction, data presentation and drawing conclusions. The results show that the use of digital marketing has an impact, namely it can increase the income of Gayo coffee farmers, Pepalang village, Takengon city. The data analysis technique uses the process of data reduction, data presentation and drawing conclusions. The results show that the use of digital marketing has an impact, namely it can increase the income of Gayo coffee farmers, Pepalang village, Takengon city.